Health effects of fruit juices and beverages with varying degrees of processing - Xinyue Zhang; Xiaojun Liao; Yongtao Wang; Lei Rao; Liang Zhao (Food Science and Human Wellness)
The degree of processing is rarely considered an independent factor in the health effects of fruit juices and beverages (FJBs) consumption. In fact, the consumption of ultra-processed foods has been shown to pose health risks. In this study, we first integrated 4 systems used to classify the degree of food processing and then classified FJBs into three major categories, low (minimal), moderate and high. Second, we compared the differences in attitudes towards FJBs in dietary guidelines. Third, we integrated the results of existing epidemiological surveys, randomized controlled trials, and animal experiments to explore the health risks associated with consuming FJBs. Deepening the processing of FJBs has been found to lead to an increased risk of diseases. Dietary pattern, nutrients, addition agents and consumer preferences may be influential factors. Finally, we investigated whether there were any changes in the health benefits of 100% fruit juices produced by different processing methods. In conclusion, minimally/moderately processed 100% fruit juices provide more health benefits than highly processed fruit beverages. The results support the need to consider the extent of FJBs processing in future studies to adjust official nutritional recommendations for beverage consumption.